2018
DOI: 10.1200/jgo.17.00103
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Clinical Breast Evaluations in a Lower Middle–Income Country Setting: An Approach Toward Achieving a Sustainable Breast Health Program

Abstract: PurposeTo promote a systems-based approach for the early detection and downstaging of breast cancer at presentation in the remote mountainous region of Gorno Badakhshan Autonomous Oblast (GBAO), Tajikistan, by introducing breast cancer awareness into the community and training health care professionals in clinical breast evaluation (CBE).MethodsThrough a public-private partnership between the Ministry of Health, the Aga Khan Health Services, Tajikistan, and the Aga Khan Health Board, we organized breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…28,43 The studies that did demonstrate change at higher levels showed improved networks, procedures, and policy. 26,27,[29][30][31][32][33][34][35]37,38,40,[44][45][46] Theoretically and practically, little evidence supports the view that only providing training to a group of individuals will genuinely build capacity. 12 This suggest that although existing evidence indicates that T3 modalities are effective in engendering sustainable change at the foundational level, it is limited in autonomously affecting the organizational and institutional levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28,43 The studies that did demonstrate change at higher levels showed improved networks, procedures, and policy. 26,27,[29][30][31][32][33][34][35]37,38,40,[44][45][46] Theoretically and practically, little evidence supports the view that only providing training to a group of individuals will genuinely build capacity. 12 This suggest that although existing evidence indicates that T3 modalities are effective in engendering sustainable change at the foundational level, it is limited in autonomously affecting the organizational and institutional levels.…”
Section: Discussionmentioning
confidence: 99%
“…The T3 training spanned various health topics, including mental health, disaster management, chronic diseases, infection control, occupational health and safety, improvement in medical procedures and processes, and health leadership development. The prominent topic area revolved around maternal and child health (see 26,27,29,46 All but two studies demonstrated change effect at their respective levels. The studies exhibiting no change consisted of examining change attributed to reducing organizational or institutional mortality or case fatality rates.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of CBE has been established in LICs. 35,37 Our argument is not that CBE is a good screening tool but that it is a more pragmatic choice than mammography in LICs. For screening programs to be effective and affordable, high-quality treatment must be available.…”
Section: Recommendationsmentioning
confidence: 94%
“…Preliminary data from trials in low-income settings suggest that CBE screening can lead to downstaging of breast cancer, although its effect on mortality hasn't been shown. 34,35 Because a substantial proportion of women in LICs present with late-stage breast cancer, 29,36 for women like Ms P and others in LICs, downstaging is critical.…”
Section: Screening For Asymptomatic Disease Vs Early Detection Of Symmentioning
confidence: 99%